Verifikasi Koordinat Titik Dasar Teknik Orde 3 dengan Pengukuran GNSS Real Time Kinematic Menggunakan Stasiun CORS Geodesi UNDIP di Kota Semarang - Arinda Yusi Madena; L. M. Sabri; Bambang Darmo Yuwono (Departement Teknik Geodesi Universitas Diponegoro, 2014)
One of the tasks of BPN in Indonesia is doing the measurement of a Horizontal control points. The result of the measurement is a monument which has a definitive and coordinate values are implicitly understood by the term static datum. But in actual fact the Earth is dynamic and can be quantified as well, the position of the monument base or point of technique to physically change from time to time, consequently the coordinates values will change.Associated with these problems, in this final task has been carried research measurement Basic Point of Technique of Order 3 by using the system of CORS (Continuously Operating Reference Station). By conducting measurements of GNSS RTK method on the basic point of the order of 3 techniques analyzed how big a difference the coordinates of the measuring results and coordinates BPN.The results of this research show that result of plotting vector different coordinate value of Basic Point of Technique of Order 3 measurements of GNSS Real Time Kinematic method against of Basic Point of Technique of Order 3 BPN is not systematic in coordinate value. Keywords: Basic Point of Technique of Order 3, CORS, RTK.